Novel modification of growth medium enables efficient E. coli expression and simple purification of an endotoxin-free recombinant murine hsp70 protein - Zachová, Kateřina; Křupka, Michal; Chamrád, Ivo; Běláková, Jana; Stuchlová Horynová, Milada; Weigl, Evžen; Šebela, Marek; Raška, Milan (Journal of microbiology and biotechnology, 2009)
Heat shock protein 70 kDa (hsp70), a molecular chaperone involved in folding of nascent proteins, has been studied for its ability to activate innate and specific immunity. High purity hsp70 preparation is generally required for immunization experiments, because endotoxins and other immunologically active contaminants may affect immune responses independently of hsp70. We have developed a novel modification of E. coli-expression medium that enabled a simple two-step production and purification method for endotoxin-free recombinant hsp70. During Ni-NTA-based affinity purification of hsp70, a contaminating protein from host E. coli cells, L-glutamine-D-fructose-6-phosphate aminotransferase (GFAT), was identified. By testing various compounds, supplementation of growth medium with a GFAT metabolite, N-acetylglucosamine, was found to reduce GFAT expression and increase the total hsp70 yield five times. The new protocol is based on column purification of His-tagged hsp70 protein produced by E. coli with the modified medium, followed by endotoxin removal by Triton X-114 extraction. This approach yielded hsp70 with high purity and minimal endotoxin contamination, making the final product acceptable for immunization experiments. In summary, a simple modification of growth medium allowed production of recombinant mouse hsp70 in high yield and purity, thus compatible with immunological studies. This protocol may be useful for production of other His.
Keywords: glutaminfruktosa-6-fosfáttransaminasa (izomerizující); chromatografie afinitní; myši; proteiny tepelného šoku HSP70; acetylglukosamin; Recombinant Proteins; kultivační média; Endotoxins; Chromatography, Affinity; Industrial Microbiology; Culture Media; Acetylglucosamine; Mice; Animals; HSP70 Heat-Shock Proteins; zvířata; Glutamine-Fructose-6-Phosphate Transaminase (Isomerizing); rekombinantní proteiny; endotoxiny; průmyslová mikrobiologie; Escherichia coli